FEMINISM IN SUSANNAH GRANT™S FILM œERIN BROCKOVICH - Sundari, Ade Lina; Bahri, Syamsul; Lubis, Fauziah Khairani (Universitas Negeri Medan, 2020)
The research is about feminism in the film œErin Brockovich. This study aims at identifying what the type and the principles of the feminism found in Erin Brockovich™sFilm. This study is conducting by applying descriptive qualitative method. The source of data is taken from the film and script. The techniques for analyzing the data are descriptive qualitative research. The writer uses Tong™s Theory to analyze the type of feminism and Sadli™s Theory to analyze the principles of feminism. This film is based on a true story; Erin Brockovichdescribes a single mother of three children who succeed in lawsuit office that helps many people of the PG&E case in Hingkley. The role of Erin shows a super mother who can be equal both take care of her children and succeeds in her career. The results of this research show that there are 30 dialogues and scenes it refers to Liberal Feminism. Then, from 50 dialogues and scenes, it was found there are all out of four types of the principles of feminism, they are: daring to convey a different opinion, having clearer aspirations and ambitions, having a desired social status, and daring tocompete.